Quality of life among patients with chronic non-communicable diseases during COVID-19 pandemic in Southern Ethiopia: A cross-sectional analytical study - Ayalew, Mohammed; Deribe, Bedilu; Hussen, Siraj; Defar, Semira; Gedefaw, Abel (Frontiers in Psychiatry, 2022)
Background The COVID-19 outbreak became a continuing global health agenda. It has a significant impact on individuals’ quality of life (QOL). Patients with preexisting medical conditions may have severely reduced QOL. The aim of this study was to assess QOL and its associated factors among patients with chronic non-communicable diseases (NCDs) during COVID-19 pandemic at Sidama Regional State, southern Ethiopia. Methods We conducted a multicenter, cross-sectional study from 1 June to 1 September 2021. A total of 633 participants took part in the study, using an interviewer-administered structured questionnaire. The QOL was measured using the World Health Organization Quality of Life (WHOQOL-BREF) Scale, which has 12 items. To describe different variables, descriptive statistics were employed. To find independent factors associated with QOL, we used multivariable linear regression analysis. P-value of < 0.05 was declared statistically significant at 95% confidence interval (CI). Results The majority (56.4%) of participants were male and about half (53.1%) had a diagnosis of diabetes mellitus. The multivariable linear regression model showed statistically significant negative association between different independent variables such as age (β = −0.188, 95% CI = −0.238 to −0.139), being female (β = −1.942, 95% CI = −3.237 to −0.647), duration of illness ≤ 5 years (β = −4.222, 95% CI = −6.358 to −2.087), alcohol use in the past 3 months (β = −4.574, 95% CI = −6.905 to −2.243), common mental disorder (CMD) (β = −1.512, 95% CI = −2.924 to −0.100), insomnia (β = −0.274, 95% CI = −0.380 to −0.168), and QOL. Also, there is a statistically significant positive association between QOL and being illiterate (β = 3.919, 95% CI = 1.998–5.841) and living in the rural area (β = 2.616, 95% CI = 1.242–3.990). Conclusion In general, the findings confirmed that the COVID-19 pandemic had a negative impact on patients with chronic NCDs QOL. The QOL was significantly influenced by age, gender, educational status, residence area, duration of illness, alcohol use, CMD, and insomnia during COVID-19 pandemic. Thus, this study suggests that addressing insomnia, co-morbidities of mental disorders, and alcohol use has the potential effect to improve the QOL of patients with chronic medical illnesses.